Instructional strategies for students with mild, moderate, and severe intellectual disability - Gargiulo, Richard M.; Bouck, Emily C. (Los Angeles, CA : SAGE Publications, Inc., 2018)
Key Features Involves not only a focus on elementary, secondary education and transition but also preschool education as well. Addresses the whole spectrum of students with intellectual disabilities including mild, moderate and severe intellectual disability. A discussion of assistive technology throughout the chapters reflects technology's increased usage to support students with intellectual disability. Chapters have been written by leading experts in the respective content.
Includes bibliographical references and index.
Description based on XML content.
Keywords: Children with mental disabilities -- Education